Spatiotemporal characteristics of precipitation in Harbin City, China, from 1962 to 2020 - Fu, Yuanyuan; Sun, Jichao (Frontiers in Environmental Science, 2025)
Based on daily precipitation data from 11 stations in Harbin City from 1962 to 2020, various statistical methods, including linear regression, moving averages, anomaly analysis, Mann-Kendall (M-K) mutation test, and Morlet wavelet analysis, were applied to examine annual and seasonal precipitation trends, mutations, and periodicities. The results reveal an increasing trend in annual precipitation, with significant increase during all seasons, particularly in summer, which contributes the most to total annual precipitation. Monthly precipitation shows significant variation, with July being the wettest and January the driest. Multiple abrupt changes were identified in both annual and seasonal precipitation, with the most significant mutations occurring in 1963, 1979, and 2018. Periodic analysis indicates that the main periodicity in annual precipitation occurs at 32–52 years, with seasonal variations peaking at different scales. Spring and winter show the highest periodic intensity at 45–64 years, while summer and autumn are most strongly influenced by cycles at 32–52 years. Precipitation periodicity shortens from north to south and east to west. Precipitation also shows a strong positive correlation with vegetation indices. These findings provide valuable insights for water resource management and agricultural planning in the region, offering a scientific basis for developing strategies to address seasonal and long-term precipitation fluctuations.